Selective footprinting of 40S and 80S ribosome subpopulations (Sel-TCP-seq) to study translation and its control - Wagner, Susan; Bohlen, Jonathan; Herrmannova, Anna; Jelínek, Jan; Preiss, Thomas; Valášek, Leoš Shivaya; Teleman, Aurelio A (Nature protocols, 2022)
Multiple aspects of mRNA translation are subject to regulation. Here we present a ribosome footprinting protocol to determine the location and composition of 40S and 80S ribosome complexes on endogenous mRNAs transcriptome-wide in vivo in yeast and mammalian cells. We present an extension of the translation complex profiling (TCP-seq) protocol, originally developed in yeast, by including an immunoprecipitation step to assay the location of both 40S and 80S ribosome complexes containing proteins of interest. This yields information on where along mRNAs the ribosome-bound protein of interest joins the ribosome to act, and where it leaves again, thereby monitoring the sequential steps of translation and the roles of various translation factors therein. Rapid fixation of live cells ensures the integrity of all translation complexes bound to mRNA at native positions. Two procedures are described, differing mainly in the fixation conditions and the library preparation. Depending on the research question, either procedure offers advantages. Execution of a Sel-TCP-seq experiment takes 5-10 working days, and initial data analysis can be completed within 2 days.
Keywords: Saccharomyces cerevisiae; RNA, Messenger; Protein Biosynthesis; savci; proteosyntéza; Ribosomes; Animals; Mammals; messenger RNA; zvířata; ribozomy